Made In China 2025 and New Trends of Entrepreneurship Educationof China: A Socio-Economic-Educational Perspective (Asian Education Studies, 2016)
The importance of entrepreneurship for economic growth and job creation has gained wide acceptance around the world. The Chinese government is dedicated to innovation and entrepreneurship, realizing the critical importance in meeting this dual purpose lies in entrepreneurship education (EE) and its integration across the government, academic and business sectors. This paper outlines the emergence of entrepreneurship and the emerging trends in EE of China by looking at the past and present of China’s economy, education and government policies through a socio-economic-educational perspective. It focuses on Made In China 2025, an important 10-year national plan, that outlines China’s objectives in future economic development, and the future directions for China’s EE. By looking at past and emerging trends this study presents a historical and current picture of EE within China. The socio-economic-educational perspective of this study results in the following observations: the change from government programmed economy to a more open briskness driven economy, the close relationship between China’s reform in economy and education, the impact of government policies and mandates on China’s entrepreneurship education, EE in China, a new facet of China’s education reform, which has moved from education for the elite to the masses, and lastly, Made In China 2025’s call for innovation and reform in educational practices of EE in China. The application of a socio-economic-educational perspective provides for broader and deeper insights into the direction for the further development of EE in China.